(Invited) Fabrication of Ge Waveguides by Epitaxial Lateral Overgrowth toward Monolithic Integration of Light Sources. (18th August 2016) - Oda, Katsuya; Okumura, Tadashi; Kasai, Junichi; Kako, Satoshi; Ishida, Satomi; Iwamoto, Satoshi; Arakawa, Yasuhiko
Abstract : Ge waveguides (WGs) were fabricated on an SiO2 layer by combining epitaxial lateral overgrowth, chemical mechanical polishing (CMP), and reactive ion etching (RIE) of a Ge layer selectively grown on SiO2 patterns using low pressure chemical vapor deposition. Selectivity was promoted by increasing growth temperature; length of the epitaxial lateral overgrown Ge layer reached 5 μm on the SiO2 layer under conditions of optimal selective growth at a temperature of 750°C. The Ge layers were planarized by using CMP down to a thickness of 1 μm, and then Ge WGs as active regions for light emitting devices were formed by using RIE on the planarized Ge layers. After defective regions around the Ge/Si interface were removed, four-times-higher photoluminescence was obtained from the Ge WGs compared with one that contained the Ge/Si interface. These results indicate that this combined technique efficiently improved the performance of Ge light-emitting devices.